Maintaining the purity of environment : conserve the sustainable use of marine and coastal ecosystem at Tanjung Dawai, Kedah - Ridzuan, Nurnadhira (2018)
The cultural landscape is landscapes that have been affected, influenced, or shaped by human involvement. Collectively, cultural landscapes are works of art, narratives of culture, and expressions of regional identity. The purpose of this project was to explore the context of the cultural landscape in the viewpoint of the landscape field for maintaining the purity of environments at Tanjung Dawai, Kedah. In order to study the problem of Tanjung Dawai, two sites have been selected as case studies such as Kilim Karst Geoforest Park, Langkawai and Vung Ro Bay, Vietnam. Despite the significance of Tanjung Dawai, marine and coastal ecosystem there are severely affected by various human activities that carry out non-sustainable development, particularly land reclamation, aquaculture and industrial activities near the coast. This problem solved by conserving the sustainable use of marine and coastal ecosystem as well as the sustainable design proposal emphasizes on the collaboration of sustainable design treatment into existing cultural landscape features in a traditional village. Tanjung Dawai with a small town have a long time of created a significant sense of place with local, character, based on the natural, built and cultural heritage. The unique history and identity have provided the village itself street patterns that reflect the layout of early settlements. These settlements were also an important market and social centre for the surrounding rural areas. Sense of place created by a village’s cultural heritage links directly to a community’s sense of identity, which can be ultimately enhanced people’s overall sense of being and belonging and quality of life. Through recommended design strategies, design principles, and comprehensive master plan, it is aimed to enhance local culture, historical value and other natural features and with dignity, respect and nurture local that minimize negative social, economic and environmental impacts.